Class Leader - Higher Human Virtues, Skilled Teacher - Salomov Gulom Yuldashevich (Genius Publishing Group, 2022)
Upbringing, educational hour, spiritual, life, spirituality, content, friendly, social, moral, virtue, labor, aesthetic, emotional, mind, behavior, political, ideological, education, society, state, person, process, activity, worldview, knowledge, feature, national, value, tradition, tradition, future, prospect, independence, independence, pride, pride, physical, intellectual, intellect, technology, will.
Keywords: laboratory classes; educational standards; skills of experimental